Harmonia cromática em animações: a cor no contexto da tecnologia - Franck, Gláucia (2015)
This paper search is to demonstrate the reciprocal influence between art and technology in addition to the artifact through the use of color in obtaining the chromatic harmony and strengthening visual perceptual and cultural. We try to show how the art appropriates technology in obtaining harmony by using the color in the creative process. The art, to be mediated by technology, challenges the artist to oppose technological determinism that imposes results by standardization of the use of its gadgets, surpassing its limits in reinvention of their purposes. This work has as objective find the choices and the uses of color in the animation short films of Disney-Pixar’s as materialization of meanings in the construction of a narrative, highlighting the opposition between the relational context and instrumental of technology by overcoming its limits reinvented itself by using the color in order to reinforce the meanings offered by this narrative. Initially we will be presenting assumptions likely to find technology in their conceptual dimensions starting from the axis color that permeates throughout the work, the main focus will be on the concepts of the theory of color essential for to this understanding, and finally, armed with the theoretical framework, we will analyze the images and complete our survey. To carry out this research work in qualitative approach we performed the analysis of the images of the sample selected intentionally within specific criteria prioritizing images that suffered from the predetermined characteristics.